2016
DOI: 10.3389/fmars.2016.00182
|View full text |Cite
|
Sign up to set email alerts
|

Uses of Innovative Modeling Tools within the Implementation of the Marine Strategy Framework Directive

Abstract: In Europe and around the world, the approach to management of the marine environment has developed from the management of single issues (e.g., species and/or pressures) toward holistic Ecosystem Based Management (EBM) that includes aims to maintain biological diversity and protect ecosystem functioning. Within the European Union, this approach is implemented through the Marine Strategy Framework Directive (MSFD, 2008/56/EC). Integrated Ecosystem Assessment is required by the Directive in order to assess Good E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 134 publications
0
23
0
Order By: Relevance
“…Monitoring data are also important for development and validation of ecological models. Ecological models have capabilities to evaluate ecosystem structure and function, involving impacts of human activities, and are potentially valuable aids in environmental management (Piroddi et al, 2015;Lynam et al, 2016;Tedesco et al, 2016). Moreover, in our scenarios, even good knowledge prior to the management decision indicated that additional information would be beneficial.…”
Section: Discussionmentioning
confidence: 92%
“…Monitoring data are also important for development and validation of ecological models. Ecological models have capabilities to evaluate ecosystem structure and function, involving impacts of human activities, and are potentially valuable aids in environmental management (Piroddi et al, 2015;Lynam et al, 2016;Tedesco et al, 2016). Moreover, in our scenarios, even good knowledge prior to the management decision indicated that additional information would be beneficial.…”
Section: Discussionmentioning
confidence: 92%
“…The EU has implemented this through the MSFD (Council Directive, 2008/56/EC), which aims to maintain biodiversity and protect ecosystem function with modeling being required at each step of the assessment cycle (Lynam et al, 2016). Beyond improving our assessments of state, models are an integral part of the decision-making process, since they allow assessment of the performance of policies and potential management measures alongside quantification of the risk and uncertainty (Hyder et al, 2015a;Lynam et al, 2016). Models can also be used to assess the value of different configurations of monitoring networks, although further development is required in this area (Kupschus et al, 2016).…”
Section: Optimizing Marine Monitoring Modeling In Current Monitoring mentioning
confidence: 99%
“…There are some significant challenges surrounding the uptake and use of complex models by decision makers (Hyder et al, 2015a;Lynam et al, 2016) relating to understanding of models in the following ways; production of functional outputs, quantifying uncertainty, and availability of quality standards. The availability of products and decision making timescales are often at odds with model development (Hyder et al, 2015a;Queirós et al, 2016).…”
Section: Optimizing Marine Monitoring Modeling In Current Monitoring mentioning
confidence: 99%
“…In marine science numerical models, and especially ecosystem models, have developed into an important tool for policy advice and environmental management applications (Rose et al, 2010;Holt et al, 2014;Robson, 2014;Lynam et al, 2016). The predictive capabilities of these models, in particular under changing environmental conditions, naturally rely strongly on the model formulation, including choice of functional groups and the form of their representation, i.e., their parameterisation.…”
Section: Modeling the Plankton-enhancing The Integration Of Biologicamentioning
confidence: 99%
“…Increasing data and information use have been suggested as a step toward improving management applications (Dyble et al, 2008;Lynam et al, 2016). Everett et al present a review on the current practices in zooplankton observation and modeling.…”
Section: Modeling the Plankton-enhancing The Integration Of Biologicamentioning
confidence: 99%